2007
DOI: 10.1007/s00198-006-0322-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of persistence and compliance with bisphosphonates for osteoporosis

Abstract: Although patients using weekly bisphosphonate medication follow their prescribed dosing regimens better than those using daily therapy, overall compliance and persistence rates were suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
257
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(294 citation statements)
references
References 28 publications
26
257
0
11
Order By: Relevance
“…However, it has been shown that the mode and schedule of administration may affect persistence and compliance with therapy and, in particular, less frequent regimens have been associated with better adherence. [16,63] Therefore, persistence rates for twice-yearly injections of denosumab would be higher than those previously reported for daily or weekly bisphosphonates. This has been recently confirmed by an open-label study of 250 osteoporotic women who were randomized to either denosumab or branded oral alendronate.…”
Section: Cost Effectiveness Of Denosumab For Post-menopausal Osteopormentioning
confidence: 82%
“…However, it has been shown that the mode and schedule of administration may affect persistence and compliance with therapy and, in particular, less frequent regimens have been associated with better adherence. [16,63] Therefore, persistence rates for twice-yearly injections of denosumab would be higher than those previously reported for daily or weekly bisphosphonates. This has been recently confirmed by an open-label study of 250 osteoporotic women who were randomized to either denosumab or branded oral alendronate.…”
Section: Cost Effectiveness Of Denosumab For Post-menopausal Osteopormentioning
confidence: 82%
“…9 In the UK there is a move towards adopting 20 per cent risk for any osteoporotic fracture and 5 per cent for hip fracture. Fixed treatment thresholds for people in the UK are attractive as they are easy to use and allow clear division into low risk (less than 10 per cent for any fracture and 3 per cent for hip fracture), intermediate risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) per cent for any fracture and 3-5 per cent for hip fracture) and high risk (>20 per cent for any and >5 per cent for hip fracture). In the absence of national guidance, the decision as to which treatment threshold to use needs to be agreed locally.…”
Section: Splmentioning
confidence: 99%
“…Adherence to oral medications to reduce fracture risk is generally poor, with approximately one-third to a half of people prescribed bisphosphonates having low or nonadherence. 16 This poor adherence is associated with an increased risk of fracture 17 and compliance should be reviewed at each encounter, with efforts made to find more acceptable agents where necessary, such as parenteral agents.…”
Section: Challenges Of Bone Protective Therapymentioning
confidence: 99%
“…Uyum eksikliği tüm tedavilerde önemli bir konudur; kronik hastalıklar ve OP bir istisna değildir. Osteoporotik hastalarda bir yıllık tedavide hastaların uyum oranları %26 ile %70 arasında değişmektedir (32). Tamamen veya neredeyse tamamen uyumlu hastalarla karşılaştırıldığında, uyum eksikliğinin kırık riskinde artışı ile ilişkili olduğu gösterilmiştir (33,34).…”
Section: Tedaviye Yetersiz Yanıtı Olan Hastalara Yaklaşım Nasıl Olmalı?unclassified